Putting the financial system to work for the poor and SMEs - Abdul Magid Osman; Djamila Pontes Osman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The financial inclusion effort achieved positive results, with the number of Mozambicans having access to banking services increasing considerably, particularly after 2011- 12. However, the economic and social impact was limited, considering that farm productivity has remained low and poverty levels are still high. The neoliberal doctrine in the economic sphere, its expression in the restrictive monetary policies, and the weakness of the multi-party democracy system have been institutional factors restricting economic and social development. Consequently, this study proposes some institutional reform measures to expand credit to family subsistence farmers, small and medium-sized enterprises, the population in general, and low-income families in particular. Young people could benefit from more accessible housing loans. Rural family farmers also need systemic, public support.
Keywords: G18; G20; G28; Q14; 330; credit; guarantees; financial inclusion; small and medium-sized enterprises; rural familyfarmers